Q methodology - McKeown, Bruce (Quantitative applications in the social sciences, 2013)
Defines the distinctive set of psychometric and operational principles which, when combined with specialized statistical applications of correlation and factor-analysis techniques, provide researchers with a systematic and rigorously quantitative means for examining human subjectivity.